Prefeasibility analysis of livestock feed manufacturing in the Caribbean Community (Redma Consultants Limited TorontoCA, 1982)
Examines potential for increasing local production of animal feeds for commercial livestock within the CARICOM region. Defines potential demand for animal feed (ie. poultry, swine, dairy and beef cattle) and identifies production capacity to meet this demand, specifically the construction of two new mills in Guyana and St Vincent, each with a capacity to produce up to 50,000 tons annually. Gives economic and financial analysis for two types of mills producing at a capacity of 8 1/2 and 17 tons per hour respectively. Discusses new investments, operating costs, revenue, and return of investments.
Keywords: FEED